The moderating effect of environmental regulation and policy on the relationship between total quality management (TQM) and organizational performance in the Malaysian food and beverage companies - Diekola, Akanmu Muslim (2016)
There have been inconsistent findings in the literature concerning the relationships between TQM and organizational performance. Hence this research has prompted further investigation on the effect of other variables that may better explain the nature of these links. In the related literatures, many theories have suggested that the compatibility between strategies, resources, and capabilities are the keys for organizational success. The main purpose of this study is to investigate the moderating effects of environmental regulation and policy (ERP) on the relationship between total quality management (TQM) and organizational performance (OP). Quality assurance (QA) and continuous process improvement (CPI) as TQM elements considered in this study were moderated with their respective relationships with organizational performance. Therefore, to achieve this purpose, this study has integrated different theories such as the contingency and the institutional theories in order to provide the effect of QA and CPI on successful strategy implementation. Questionnaires were distributed to 250 Malaysian food and beverages companies. 71 questionnaires were returned and used in the analysis using the PLS-SEM. Studies revealed that TQM can be divided into the management or soft aspects (management concepts and principles) of TQM and the technical or hard aspects (management tools and techniques) of TQM . This study is exclusively based on the soft elements of TQM. The results of this study revealed that QA and CPI have always been significant predictors of organizational performance by following the regulations and policy related to environment. More importantly, the results have also confirmed the moderating effect of environmental regulation and policy on the relationships between TQM and organizational performance. This study also supported the premises of the contingency theory and the institutional theory by reaffirming the importance of the supportive ERP for any successful strategy implementation in enhancing organizational performance through the implementation of innovative practices. However, this result cannot be generalized as data were collected through a cross-sectional approach. Future research can extend it to longitudinal research